Post-nucleation evolution of the liquid–solid interface in nanowire growth. (17th December 2021) - Maliakkal, Carina B; Jacobsson, Daniel; Tornberg, Marcus; Dick, Kimberly A
Abstract: We study using in situ transmission electron microscopy the birth of GaAs nanowires from liquid Au–Ga catalysts on amorphous substrates. Lattice-resolved observations of the starting stages of growth are reported here for the first time. It reveals how the initial nanostructure evolves into a nanowire growing in a zincblende ⟨111⟩ or the equivalent wurtzite⟨0001⟩ direction. This growth direction(s) is what is typically observed in most III–V and II–VI nanowires. However, the reason for this preferential nanowire growth along this direction is still a dilemma. Based on the videos recorded shortly after the nucleation of nanowires, we argue that the lower catalyst droplet-nanowire interface energy of the 111 facet when zincblende (or the equivalent 0001 facet in wurtzite) is the reason for this direction selectivity in nanowires.